Investigation of rheological behavior of produced HSTF and evaluation of energy dissipation performance by application to Twaron fabric - Yanen, Cenk; Solmaz, Murat Yavuz; Aydogmus, Ercan; Arslanoglu, Hasan (Springer, 2023)
In this research, the rheological behavior of shear thickening fluid (STF), produced using many nanoparticles, has been investigated. Fumed silica, multi-walled carbon nanotube (MWCNT), graphene nanoplate (GFNP), and silicon carbide (SiC) nanoparticles have been used in the production of the hybrid sample. In the rheological test results, it has been preferred because it is successful in the production of hybrid shear thickening fluid (HSTF), 25 wt.% by the mixture of Aerosil 150, and polyethylene glycol 400 (PEG 400). Different particle sizes of each nanoparticle have been determined by adding MWCNT, GFNP, and SiC nanoparticles to HSTF. In the production of HSTF, the highest performance is found in MWCNT (0.3 wt.%), SiC (0.2 wt.%), and GFNP (0.1 wt.%) when each nanoparticle is used as a single, double, or triple. The stab resistance of Twaron fabrics is also investigated in a drop tower against spike and knife impactors. It is understood that HSTF-impregnated Twaron fabrics have a positive effect on energy absorption performance. The energy absorption performance of HSTF-impregnated Twaron fabrics is found to be more effective than STF-impregnated Twaron fabrics.
Keywords: Shear thickening fluid; Rheological behavior; Stab resistance; Energy absorption performance